Durability and Sustainability Assessment of Cow Dung Ash–Wood Ash Concrete Exposed to Acid–Alkali Cycles - Umar, Auwal Abdullahi (Journal of Multidisciplinary Research Advancements, 2026)
This research investigates the durability and sustainability performance of concrete incorporating agro-waste ashes—cow dung ash (CDA) and wood ash (WA)—as partial cement replacements under aggressive acid–alkali cycling. A 1:1 blend of CDA and WA was used to replace ordinary Portland cement (OPC) at 0%, 10%, 15%, 20%, 25%, and 30% by weight across six mix designs. Concrete specimens were cured for 7, 14, 28, 56, and 90 days and then exposed to alternating sulfuric acid (pH ≈ 2) and sodium hydroxide (pH ≈ 12) solutions for up to 90 days to simulate harsh environmental conditions. Tests conducted included slump measurement, compressive strength before and after exposure, mass loss, and visual inspection. Statistical analysis (ANOVA) and regression modeling were employed to evaluate the influence of mix variables on durability indicators. Results demonstrated that mixes with 10–15% replacement achieved the best overall performance, showing enhanced durability and strength retention. The 10% blend attained a compressive strength of 31.6 MPa at 90 days and retained over 72% of its original strength after chemical exposure. Weight loss and mass change were significantly lower compared to the control. Regression models showed strong predictive capability (R² > 0.99), supporting the reliability of the developed equations. This study highlights the potential of CDA–WA blends as sustainable pozzolanic materials that enhance chemical resistance in concrete while promoting circular economy goals. The findings provide practical insights for integrating agro-waste materials into eco-efficient construction, especially in chemically aggressive environments.